SEARCHING FOR NEW AUTHORITARISM IN THE CONDITIONS OF GEOPOLITICAL TURBULENCE - Шаповаленко, М. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2020)
The main factors of the growing popularity and influence of undemocratic regimes are considered. In the modern world, in the context of geopolitical turbulence, the geopolitical centers of power and actors in the adoption of global management decisions are changing. But there is a need to manage socio-political and economic processes for the stable development of society. Therefore, the conditions of chaos only strengthen the attempts to search and create fuses for the uncontrollability of the development of the political regime. Especially in the conditions of the crisis of the formal institutions of liberal democracy, a clear proof of which was the emergence of post-democracy as a phenomenon and process of evolution of «modern» democracies. Several factors reinforce this trend. First of all, the reverse wave of democratization (S. Huntington), which lasts several decades. Secondly, the crisis of American hegemony and the completion of the next cycle of political hegemony. We must add the completion of the macrohistorical cycle of the internal political development of the political system of the USA itself (A. Schlesinger) with a number of crises throughout the entire first half of 2020. The weakening of the global hegemon resulted in the process of easternization and the emergence of new geopolitical centers (primarily, Asia, namely China with a powerful economy, which is a prerequisite for the formation of a new hegemon). The third factor is the growth of right-wing extremism and right-wing populism in countries of sustainable democracies and new democracies. The wave of populism is supported by a conservative turn in the form of legal consolidation of nationalism, the legitimation of the dominance of the collective over the individual. Another factor of destabilization is the crisis of traditional institutions of democracy, primarily political parties, party leaders who can refuse program promises and turn into lawyers of the «expression of the will of the people». Amid growing mistrust of traditional democratic institutions and the values of liberalism, there is a growing demand for leaders and institutions that can ensure the safe and stable development of society. And the actual uniqueness of the current development is the search for new forms of coexistence of authoritarian and democratic institutions within the same political regime.